Business models and key success drivers of agtech start-ups - Lohento, Ken; Sotannde, Motunrayo (Technical Centre for Agricultural and Rural Cooperation, 2019)
This interpretative phenomenological research focuses on youth-led companies offering digital services to the agrofood sector in West Africa. Youth is considered as per the African Union definition: individuals aged between 15 and 35 years old. Our research questions were to understand the business models adopted by these start-ups; how their business models and business model innovation lead to business success; other key drivers that can support the achievement of success. With this study, we aim to contribute to the limited existing body of knowledge on this nascent but growing business field in West Africa. Though focused on West Africa, analyses go beyond and are of interest to any stakeholders interested in this subject in Africa in particular.